Hieracium racemosum subsp. spinidentatum (Asteraceae), a new hawkweed from Lombardy, Italy - Gottschlich, Günter; Villa, Milena (Phytotaxa, 2022)
A new hawkweed endemic to Northern Italy, Hieracium racemosum subsp. spinidentatum, is described and illustrated. Information on its morphology, distribution, ecology and taxonomic relationship is provided.